The Influence of Brand Image and Product Quality on Purchase Decisions of Nike Air Jordan Shoes at FMS Store Surabaya - Syam, Fakhmy; Utomo, Priyo (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: This study aims to analyze the influence of brand image and product quality on the decision to purchase Nike Air Jordan Footwear is no longer regarded merely as a functional necessity; it has evolved into an expression of identity, a status symbol, and an integral element of urban lifestyles at FMS Store in Surabaya. Design/Methodology/Approach: This study uses a quantitative approach with a survey method. The research respondents are consumers who have purchased Nike Air Jordan shoes at the FMS Store in Surabaya. A total of 81 samples were obtained, selected using purposive sampling based on product purchase experience criteria. The research instrument was a questionnaire with a 4-point Likert scale to measure the variables of brand image, product quality, and purchasing decisions. Data analysis was performed using the Partial Least Square (PLS) approach through SmartPLS 4.0 software, which included outer model testing (validity and reliability) and inner model testing (R-square and hypothesis testing with bootstrapping). Findings: The results showed that brand image had a positive and significant effect on purchasing decisions with a t-statistic value > 1.96 and p-value < 0.05. Product quality was also proven to have a positive and significant effect on purchasing decisions, with the research indicators meeting the validity and reliability criteria (AVE > 0.5 and Composite Reliability > 0.7). The R-square value of 0.65 indicates that brand image (X1) and product quality (X2) together explain 65% of the variation in purchasing decisions (Y1), while the rest is influenced by other factors outside the scope of this study. Research limitations/implications: This study is limited to respondents from FMS Store in Surabaya with a relatively small sample size, so its generalizability is still limited. Theoretically, the results of this study reinforce consumer behavior theory that brand image and product quality play an important role in shaping purchasing decisions. Practical implications: For FMS Store management, the results of this study provide input to continue strengthening the Nike Air Jordan brand image and maintaining product quality as a strategy to increase customer satisfaction and loyalty. Originality/value: This study provides empirical contributions by examining the factors that influence the decision to purchase Nike Air Jordan shoes in the context of local reseller in Surabaya, which has rarely been studied.